2017
DOI: 10.1177/1352458517707346
|View full text |Cite
|
Sign up to set email alerts
|

Pittsburgh compound-B PET white matter imaging and cognitive function in late multiple sclerosis

Abstract: PiB uptake in the cortex in late MS is not different from normal age-matched controls. PiB uptake in the WM in late MS may be a marker of the large network structures' integrity such as those involved in visuospatial performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 44 publications
(67 reference statements)
6
41
0
1
Order By: Relevance
“…After computation of voxel-wise maps of the distribution of volume ratios reflecting myelin content, the authors calculated dynamic indices of global myelin content, demyelination and remyelination in each patient. A progressive reduction in 11 C-PiB binding from the NAWM to MS lesions, reflecting a decline in myelin content was demonstrated and dynamic remyelination was inversely correlated with clinical disability [23]. These findings support the role of AMY-PET with 11 C-PiB in the evaluation of remyelination potential at the single-subject level.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…After computation of voxel-wise maps of the distribution of volume ratios reflecting myelin content, the authors calculated dynamic indices of global myelin content, demyelination and remyelination in each patient. A progressive reduction in 11 C-PiB binding from the NAWM to MS lesions, reflecting a decline in myelin content was demonstrated and dynamic remyelination was inversely correlated with clinical disability [23]. These findings support the role of AMY-PET with 11 C-PiB in the evaluation of remyelination potential at the single-subject level.…”
supporting
confidence: 68%
“…These studies demonstrated that AMY-PET detects decreased activity in black hole areas in T1weighted MR images and in WM lesions in T2-weighted MR images, suggesting that amyloid tracer uptake decreases with demyelination. 11 C-PiB has been shown to bind more strongly to NAWM than to perilesional tissue and lesions, in line with the relative loss of myelin in these regions [22][23][24]. Furthermore, longitudinal data support the hypothesized ability of 11 C-PiB to capture demyelination and remyelination in single lesions over time.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Studies using MRI to measure white matter hyperintensity have proposed that cerebral small-vessel disease can lead to reduced Ab clearance and to increased cerebral GM 11 C-PiB in AD (33,34). However, white matter hyperintensity measurements in studies of WM 11 C-PiB uptake have found reduction in binding (35) and that WM lesions can reduce WM 11 C-PiB binding in cognitively impaired (36) as well as in multiple sclerosis patients (37).…”
Section: Discussionmentioning
confidence: 99%
“…For all indices high between-patient variability of myelin content change was highlighted during follow up and dynamic remyelination was demonstrated to inversely correlate with clinical disability scales. The association of cognitive function in late MS with cortical and WM PiB binding has also been assessed in another group of 24 MS patients identified within the population-based Mayo Clinic Study of Aging (Zeydan et al 2018). In that study Zeydan and colleagues found no difference in global cortical PiB standardized uptake value ratios between MS and controls.…”
Section: Pet Tracers For Myelin Kineticsmentioning
confidence: 99%